Inheritance of selected quantitative attributes in lablab bean (Lablab purpureus L.) - Raihan, MS; Newaz, MA (Bangladesh Journal of Plant Breeding and Genetics, 2011)
Bangladesh Journal of Plant Breeding and Genetics, Vol.22(1) June 2009 p.53